Research on Safety Risks of Speech Information - H. V. Davydau; V. A. Papou; A. V. Patapovich; Ye Li; Xiaoming Wu; Fuqiang Wang; Peng Zhang; Xiaoyan Bi (Цифровая трансформация)
The paper presents the results of research on the assessment of the security risks of speech information. It is shown that for speech information circulating in an acoustic form in a room, the main indicator of security is confidentiality. Confidentiality is determined by an indicator equal to 1, when complete confidentiality of speech information is provided, and an indicator equal to 0, when information has lost confidentiality, there are no intermediate values of this indicator. It is shown that the loss of confidentiality of speech information can occur due to the implementation of at least one of the possible threats. Methods for assessing the security risks of speech information are considered. For speech information, security risks consist of the risks of leakage through acoustic channels outside the security area of the room and the risks associated with the human factor, since the carrier of speech information is also a person. The risks associated with the leakage of speech information through acoustic channels are considered in details. The mechanism for ensuring zero risk of leakage of speech information through the acoustic channel is considered and specific recommendations for its implementation are given.